Lead and Other Elements in Date Palm(Phoenix dactyliferaL.) Fruits (Dates) - Al-Shayeb, S.M. (Asian Journal of Chemistry, 2010)
The date (fruit) of date palm (Phoenix dactylifera .L )has been analyzed for lead and other metal pollutants in Riyadh City, Saudi Arabia. The content of (Pb, Zn, Cu, Ni, Cr and Li) was determined for washed and unwashed dates (fruit) samples collected from five different sites with different degrees of metal pollution (three roads, area flooded with treated sewage water "Al Hayer area" and rural "control" area). The analysis of P. dactylifera fruit (dates) showed the date samples to be superficially polluted by lead and zinc and slightly by copper compared with the control area However, merely washing the fruit by water can remove about 80% of the lead and reduce lead content in fresh date fruit from 1.16 to 0.35 μg g–1 which is about three times less than the British legal limit for lead in food (1.0 μg g–1). Therefore, it is strongly recommended to wash those date fruits growing along side the roadways before eating.